2010
DOI: 10.2174/1874437001004010022
|View full text |Cite
|
Sign up to set email alerts
|

A General Overview on Past, Present and Future Antimycotics~!2009-11-01~!2010-04-06~!2010-06-24~!

Abstract: Since the discovery of amphotericin B in 1955 the armamentarium of antimycotic drugs now embraces many new chemical classes: azoles, allylamines and candins. However, despite the wide variety in chemical structure, there is a lack of diversity in terms of mechanism of action. The mechanism of action of the main classes of antimycotics as well as the therapeutic value of some representatives is discussed. Some challenges to innovation will be highlighted that when overcome will herald more effective therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 127 publications
(149 reference statements)
0
24
0
Order By: Relevance
“…Van Minnebruggen et al [25] concluded that "there is still an unmet medical need to further improve antimycotic therapy and that interdisciplinary research bringing together chemical, molecular and clinical expertise can help make the antimycotic drugs of tomorrow to fulfill the promise of today." One of the approaches could be genome mining of different organisms-actinomycetes and fungi in particular.…”
Section: Polyenesmentioning
confidence: 99%
“…Van Minnebruggen et al [25] concluded that "there is still an unmet medical need to further improve antimycotic therapy and that interdisciplinary research bringing together chemical, molecular and clinical expertise can help make the antimycotic drugs of tomorrow to fulfill the promise of today." One of the approaches could be genome mining of different organisms-actinomycetes and fungi in particular.…”
Section: Polyenesmentioning
confidence: 99%
“…On the other hand, there are only a few chemotherapeutic agents that can be used for life-threatening fungal infections. Natural products such as polyenes and echinocandins, and synthetic chemicals including flucytosine and azoles are currently available classes of antifungal agents 4 . Among the different classes of antifungal agents that have been discovered, azoles are first-line drugs for the treatment of invasive fungal infections, because of their high therapeutic index.…”
Section: Introductionmentioning
confidence: 99%
“…The azoles are chemically either an imidazole or a triazole ring attached to a functionalized phenethyl moiety as their pharmacophore ( Figure 1, structure A). Several new azole antifungal agents, such as luliconazole, voriconazole, pramiconazole, posaconazole, albaconazole and isavuconazole are marketed or currently in the late stages of clinical trials 4,5 . However, the extensive use of azoles has led to the development of fungal resistance which significantly reduced their efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…and Coccidioides immitis might also be able to produce fungal biofilms in humans (Cannizzo et al, 2007;Martinez and Fries, 2010). Biofilms are extracellular matrices produced by microorganisms (primarily bacteria and fungi) which help the pathogens attach to viable and non-viable surfaces (Van Minnebruggen et al, 2010). Biofilm formation in Candida albicans resulted in a 30-to 2000-fold decrease in sensitivity to certain antifungals including ketoconazole (Martinez and Fries, 2010;Vandeputte et al, 2012).…”
mentioning
confidence: 99%